TINJAUAN YURIDIS PENEGAKAN HUKUM WARGA NEGARA ASING DALAM PEMALSUAN DOKUMEN (PUTUSAN: 158/PID.SUS/2021/PT.KWG) - Stefanus Ricman Simanjuntak; Tri Sulityowati (Reformasi Hukum Trisakti, 2022)
In contravention of the law, Chandra Sat Pal, the defendant, faked immigration documents as a foreign citizen. Immigration offences as defined in Article 128 letters a and b of Law Number 6 of 2011 Concerning Immigration were among the infractions committed by the Defendant. The issue is how to prosecute foreign nationals who fabricate immigration documents and if the Karawang District Court's ruling in Case No. 158/Pid.Sus/2021 complies with legal requirements. The answer to this topic will be obtained by normative legal research, which has the characteristics of descriptive analysis utilizing secondary data, followed by qualitative analysis with a deductive method as a conclusion. Regarding cases that occurred in law enforcement, there were several articles concerning the consequences of the defendant's actions including Article 121 letter a, Article 128 letters a and b, and Article 130 of the Immigration Law. According to the author, the sentence imposed on Chandra Sat Pal is still not strict, because the implementation of the imposition of charges requested by the Prosecutor is still not comparable to the violations committed by the defendant. Therefore, the defendant should receive a punishment commensurate with the actions that have been committed by the defendant.